Experimental studies on the influence of chlorides on the combustion and agglomeration characteristics of solid propellants - Lu Liu; Geng Xu; Zhan Wen; Guoqiang He; Peijin Liu; Wen Ao (Fuel Processing Technology)
The main approach to improving the performance of aluminum-containing propellants is to promote the rupture of the oxide film on the surface of aluminum. The high melting point of the oxide film is the primary obstacle to the oxidation reaction of the internal aluminum. This study proposes the concept of using chlorides to regulate the performance of propellants by leveraging the low melting point of aluminum chloride. Firstly, all four chlorides effectively promoted the oxidation of aluminum. Secondly, the combustion intensity of the powders, from highest to lowest, was: chlorinated polyvinyl chloride -modified aluminum powder, praseodymium chloride-modified aluminum powder, sodium chloride-modified aluminum powder, micron aluminum powder, and iron chloride-modified aluminum powder. Only chlorinated polyvinyl chloride significantly reduced the ignition delay time. Regarding the burning rate of propellants, iron chloride-modified propellants exhibited the best performance, while sodium chloride propellants showed a reduction in the burning rate. In terms of propellant agglomeration characteristics, sodium chloride aggravated agglomeration, whereas the other three inhibited agglomeration. Among them, iron chloride and praseodymium chloride reduced the average particle size of the condensed combustion products by 23.5 % and 43.0 %, respectively. The experimental results of this study provided a new approach for the performance optimization of solid propellants.